2008
DOI: 10.1186/1750-1326-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Dispensable role of Drosophila ortholog of LRRK2 kinase activity in survival of dopaminergic neurons

Abstract: Background: Parkinson's disease (PD) is the most prevalent incurable neurodegenerative movement disorder. Mutations in LRRK2 are associated with both autosomal dominant familial and sporadic forms of PD. LRRK2 encodes a large putative serine/threonine kinase with GTPase activity. Increased LRRK2 kinase activity plays a critical role in pathogenic LRRK2 mutant-induced neurodegeneration in vitro. Little is known about the physiological function of LRRK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 27 publications
(26 reference statements)
7
117
0
4
Order By: Relevance
“…Drosophila LRRK2 models were also developed (21,97,98). Loss-of-function dLRRK mutants in Drosophila yielded conflicting results on locomotive motor impairment (21,97).…”
Section: Normal and Pathological Features Of Lrrk2mentioning
confidence: 99%
“…Drosophila LRRK2 models were also developed (21,97,98). Loss-of-function dLRRK mutants in Drosophila yielded conflicting results on locomotive motor impairment (21,97).…”
Section: Normal and Pathological Features Of Lrrk2mentioning
confidence: 99%
“…A second study using the same fly line did not detect motor impairment and also showed that dLRRK loss-of-function flies are resistant to the mitochondrial toxins rotenone and paraquat, but are more sensitive to general oxidative stress, suggesting a role for dLRRK in mitochondria [76]. Overexpression of dLRRKWT or Roc domain substitution R1069C (comparable to Lrrk2 R1441C in humans) using a number of different GAL4 drivers (directed to muscle, whole-body and dopaminergic neurons) produced no deleterious effects [75].…”
Section: Fly Modelsmentioning
confidence: 95%
“…63,66 In contrast, knocking out LRRK2 has no effect on dopaminergic neuronal development or maintenance. 67 Moreover, LRRK2 transgenic mouse models do not show the further pathological results, which is unclear. 15 Parkin, phosphatase, and tensin homologinduced novel kinase 1, and DJ-1…”
Section: Leucine-rich Repeat Kinase 2 Mutationsmentioning
confidence: 99%